2003
DOI: 10.1117/12.512635
|View full text |Cite
|
Sign up to set email alerts
|

Security analysis of selectively encrypted MPEG-2 streams

Abstract: Selective encryption exploits the relationship between encryption and compression to reduce encryption requirements, saving in complexity and facilitating new system functionality. Selective encryption of MPEG video streams has been proposed in a number of variations, yet has seen little application to date. Here we focus on high encryption savings, targeting 10% of the bit stream or less encrypted, moderate security in the sense that the content is degraded to the point that purchase would be preferred over c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…For an overview of selective encryption and attacks see Engel et al [7] for JPEG2000, and Lookabaugh et al [15] for MPEG-2. Specifically there are attacks which copy structurally similar symbols from one part of the bitstream to another or inject a forged version into the bitstream.…”
Section: Resultsmentioning
confidence: 99%
“…For an overview of selective encryption and attacks see Engel et al [7] for JPEG2000, and Lookabaugh et al [15] for MPEG-2. Specifically there are attacks which copy structurally similar symbols from one part of the bitstream to another or inject a forged version into the bitstream.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, if too many syntax elements containing perceptual information are left unencrypted, the security might be compromised. A lot of research [1,8,23,24,26,31,37,39,41] has shown that some perceptual information can be recovered from various kinds of unencrypted syntax elements. This problem is due to the following fact: most multimedia coding standards are designed in such a way that many syntax elements can be decoded independently without decoding other syntax elements.…”
Section: Multimedia Encryptionmentioning
confidence: 99%
“…Tang modified the order of coefficient scanning to make the technique more secure 16) . However, Uehara and Safavi-Naini 25) , and Qiao Lookabaugh et al reviewed these proposals and proposed a combination method of encryption and compression 26) .…”
Section: Related Workmentioning
confidence: 99%